Between haven and heaven in cities: A comparison between Beijing (China) and Utrecht (the Netherlands). (September 2016) - Zhao, Ying; Dijst, Martin; Chai, Yanwei
Although heterogeneity exists, Western countries can generally be characterised by a more individualistic orientation, whereas China is a more collectivist-oriented society that is undergoing a transformation. This empirical study examined socio-cultural differences between cities in China and the Netherlands in terms of companionship and urban meeting places on the basis of activity diary surveys conducted in the metropolitan areas of Beijing and Utrecht. The focus was on activity decision-making in daily life, especially on the meaning of 'feeling at home'. Companionship and relevant meeting places were controlled for socio-demographics, analysed and compared in both metropolitan areas. The results show that in Beijing, the majority of activities are undertaken with members of the nuclear and extended family, and the home ('haven') is a place for intimate contacts with family members. In Utrecht, the share of individual activities and activities undertaken with friends is much higher than in Beijing, and the home ('heaven') is open for contacts with self-selected friends. The modelling results indicate that socio-cultural differences work through various socio-demographic variables, such as gender, family structure and educational level, providing some insights for policymakers.